Entre orquídeas y ruinas : el fragmento ante la obra monumento en Los derrotados, de Pablo Montoya (2020)
This research project is framed within the limits of comparative literature since it deals with the analysis of two visual metaphors present in Los Derrotados, a novel by Colombian writer Pablo Montoya published in 2012. The first metaphor corresponds to Francisco's travel diary José de Caldas that Pedro Cadavid, Montoya's alter ego, poetically re-elaborates in chapter ten of the novel. The second concerns the photographic ekphrasis of chapter seventeen where the narrator describes and comments on a set of photographs of Andrés Ramírez, a character built on the real figure of Jesús Abad Colorado, who documents the massacres carried out by the National Army, the paramilitaries and the groups guerrillas during the period from 1997 to 2005 in different municipalities and townships of Chocó and Antioquia. Caldas's poetic diary takes the form of the herbarium based on visual transpositions that offer the reader an iconotextual reading. For its part, photographic ekphrasis takes up the broad debate about the supposed objective nature of photography and its relationship with 19th century literary realism. The analysis of these two visual metaphors is included, in turn, within a broader commentary on the fragmentary and torn condition of the novel, a condition that is proposed as an alternative to a nineteenth-century conception of the literary work as a monument of the national narrative.